Effect of using different satellite ephemerides on GPS PPP and post processing techniques - Abdel Aziz, Khaled Mahmoud; Elsonbaty, Loutfia (Geodesy and Cartography, 2021)
The orbital error is one of the errors in GPS which affect the accuracy of GPS positioning. In this research GPS broadcast, ultra-rapid, rapid and precise satellite ephemerides are used for processing different baseline lengths among some CORS stations by using the Trimble Business Center software (TBC) and different satellite ephemerides (NRCan ultra-rapid, NRCan rapid and IGS final) are tested in CSRS-PPP online application at the same CORS stations. In this research, when using TBC software for processing the different baseline lengths by using the different satellite ephemerides and compared the coordinates of CORS stations which obtained from the different satellite ephemerides with each other. The results showed that the best satellite ephemerides closest to rapid and final satellite ephemerides are the ultra-rapid (00 UTC) and ultra-rapid (06 UTC). When processing the same CORS stations which used at TBC on CSRSPPP online application by using the different satellite ephemerides it is found also that the NRCan ultra-rapid closest to final satellite ephemerides.